Technological Integration Self Efficacy (TISE) of Prospective Mathematics Teacher Students through TPACK Implementation - Refi Elfira Yuliani; Heru (LPPM Undiksha, 2024)
High self-confidence in integrating technology into learning is one of the critical aspects relevant to TPACK. This study aims to analyze prospective teacher students' Technological Integration self-efficacy (TISE) through implementing TPACK. This study uses the Didactic Design Research (DDR) method, which consists of three stages: prospective analysis that produces TPACK design (HLT) metapedadactive analysis, producing TPACK implementation, consisting of the pilot experiment and teaching experiment stages, and retrospective study. The research participants were 61 prospective mathematics teacher students. In the Prospective stage, there were 23 participants; in the pilot experiment stage, there were 8 people; and in the teaching experiment stage, there were 30 people. Based on the study results, the TISE level of prospective teacher students is in the moderate category, TPACK ability affects the TISE score. Students' knowledge of ICT greatly supports students' TISE in mastering ICT. Students with good ICT knowledge generally provide responses that are by predictions, and vice versa; weak ICT knowledge slows down the assimilation and accommodation of students in integrating technology. The study's conclusion shows that prospective teacher students must have TISE to present more meaningful learning. The increase in TPACK on teacher TPACK scores depends on the learning environment to improve competence in integrating technology.